SISTEM PEMBINAAN KARAKTER PESERTA DIDIK DI MADRASAH ALIYAH PONDOK PESANTREN HJ HANIAH KABUPATEN MAROS - Putri, Nurul Aini; Bunyamin, Andi; Darmawangsa, Andi; Mahmud, Hasibuddin; Rosmiati; Syahid, Akhmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Nurul Aini Putri, Character Development System of Students at Madrasah Aliyah Pondok Pesantren Hj. Haniah Maros (supervised by Dr. H. Andi Bunyamin, M.Pd. and Dr. H. Andi Darmawangsa, S.Ag., M.Ag). This study aims to describe the character development system of students at Madrasah Aliyah Pondok Pesantren Hj Haniah Maros Regency and describe the effectiveness of character development of students at Madrasah Aliyah Pondok Pesantren Hj Haniah Maros Regency Maros Regency. The research method used is descriptive qualitative with a phenomenal approach. Data were collected through observation, interviews and documentation, then analyzed through the stages of data collection, data reduction, data presentation and conclusion drawing. The results of the study indicate that the character development system of students at Madrasah Aliyah Pondok Pesantren Hj. Haniah in Maros Regency is implemented in an integrated manner through various strategies, namely habituation, role modeling, discipline, responsibility, independence, advice (mau'izah), a personal approach, and the application of educational rewards and punishments. The effectiveness of character development is evident in changes in students' attitudes, who are increasingly disciplined, responsible, independent, socially aware, and demonstrate better morals. Character values ​​are not only understood theoretically through the Aqidah and Akhlak subject but are also internalized through daily habits of religious activities and extracurricular activities. This research recommends that Madrasahs continue to develop a character development system through collaboration between teachers, dormitory supervisors, and parents. Teachers and supervisors are expected to be role models and creative in instilling moral values. Students are expected to maintain the discipline, responsibility, and independence that have been developed. Future researchers are advised to examine character development more broadly.